Right heart interplay with secondary tricuspid regurgitation. How can we predict clinical events?. (4th February 2022) - Lofficial, G; Chen, E; Guerin, A; Dreyfus, J; Sportouch, C; Galli, E; Oger, E; Donal, E
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: TRAP Introduction. Secondary Tricuspid Regurgitation (TR) is a turning point in cardiac diseases. Symptoms occurred too late according to the right heart reverse remodelling capabilities. The ideal timing for proposing a valve repair remains a challenge. We sought to analyse characteristics of patients with significant secondary TR, seeking for changes in parameters over time that could be related to the risk of clinical event. Material and method. We designed a prospective observational French multicentre study of 160 patients with significant secondary TR (effective regurgitant orifice area > 30 mm²) and LVEF > 40%; we collected clinical, echocardiographic, and EKG data at baseline, 1- and 2-year follow-up. All echocardiographies were centrally analyzed. The primary outcome was death or hospitalization for heart failure Results. At 2-year 95 patients (59.3%) presented the primary outcome. They had significant morphological and functional alteration of the right heart parameters. Right Atrial Volume Index (RAVI) and right ventricular free wall Strain were respectively 73mL/m² and -19.8% versus 64.7mL/m² and 22.3% in the event-free group. None of them had significant group*time interaction. In the multivariable analysis, TAPSE/sPAP ratio > 0.4 (OR = 0.41 95%CL 0.2 to 0.82) associated to RAVI > 60mL/m² (OR = 2.13 95%CL 0.96 to 4.75) were the two independent parameters that enable the fairest and parsimonious evaluation. Conclusion. We demonstrated that short analysis using RAVI and TAPSE/sPAP almost reached us to an easier patient assessment by limiting the number of involved parameters. These parameters are now to be for defining the best timing and response to interventions.